2016
DOI: 10.1159/000452091
|View full text |Cite
|
Sign up to set email alerts
|

A Review of DNA Methylation and microRNA Expression in Recurrent Pediatric Acute Leukemia

Abstract: Acute leukemia is the most common childhood cancer diagnosis and leading cause of cancer-related death among children and adolescents. Despite substantial improvements in the survival rate of childhood acute leukemia, approximately 20-40% of the patients who undergo treatment develop relapse, with a dismal one third of these patients surviving in the long term. Epigenetics plays an important role in the progression of cancer, and existing evidence suggests a role in childhood acute leukemia relapse. A better u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 58 publications
0
11
1
1
Order By: Relevance
“…Previous studies have suggested the association between pediatric ALL relapse and miRNAs, such as miR-24, miR-128b, miR-223, miR-210, miR-335, miR-130b, miR-126, miR-222, miR-345, miR-708 and miR-23a (14). However, none of the six candidate miRNAs in this study have been previously implicated in pediatric B-ALL relapse.…”
Section: Discussioncontrasting
confidence: 65%
“…Previous studies have suggested the association between pediatric ALL relapse and miRNAs, such as miR-24, miR-128b, miR-223, miR-210, miR-335, miR-130b, miR-126, miR-222, miR-345, miR-708 and miR-23a (14). However, none of the six candidate miRNAs in this study have been previously implicated in pediatric B-ALL relapse.…”
Section: Discussioncontrasting
confidence: 65%
“…Besides the metabolic and catabolic process of 5-methylcytosine was also enriched. This indicated that methylation activity in cells administrated by PQ might be enhanced, and DNA methylation could further affect gene expression by regulating miRNA synthesis (Hale et al, 2017). Otherwise, according to pathway analysis, PI3K-Akt, mTOR, RAS, TNF and MAPK signaling pathways were significantly enriched.…”
Section: Discussionmentioning
confidence: 96%
“…Aberrant epigenome has been implicated in the undesired treatment outcomes of children with B-ALL. 25,26 A study conducted on 33 pairs of samples, which were collected at diagnosis and relapse, found that DNA hyper-methylation was a hallmark of relapse samples; 905 genes were hyper-methylated in relapsed pediatric B-ALL. 27 The same study showed that different regulators of Wnt pathway and tumor suppressor genes were amongst the hyper-methylated genes.…”
Section: Omics-based Insights Into Therapy Failure In Patients With Pmentioning
confidence: 99%